Exploring Cambodian adolescents' perceptions on sex: a qualitative investigation - Yang, Youngran; Kim, Jiwoo; Park, Gloria; Thapa, Roshna (Frontiers in Reproductive Health, 2024)
Introduction Involvement in sexual activities increases during adolescence in many countries, including Cambodia. The objective of this study is to explore the perspectives and interpretations of sex held by Cambodian adolescents within the context of their social norms and culture. Methods A qualitative research design was used to conduct in-depth interviews with a purposive sample of 91 Cambodian adolescents aged between 15 and 19 years. Participants were recruited from rural areas, and data was collected through face-to-face interviews using semi-structured interview guides. Thematic analysis was used to analyze the data. Results Four themes as perspectives of sex were identified: (1) Desire: Releasing sexual desire and stress; (2) relationship: an emotional connection and demonstration of love; (3) roles: responsibilities within a woman's marital duties; and (4) values: the value of virginity and future engagement. Cambodian adolescents' perspectives and interpretations of sex were deeply influenced by their social norms and cultural values. Men typically perceived sex through the lens of instinct and pleasure, while women often emphasized a deep sense of familial duty and held premarital sex to be morally unacceptable. Discussion The findings suggest that interventions aimed at improving the sexual health of Cambodian adolescents should be designed with an understanding of the social norms and cultural values that shape their perspectives and interpretations of sex. Such interventions should focus on promoting safe sex practices and providing accurate and comprehensive sexual education.